Illusory Responses across the Lewy Body Disease Spectrum. Issue 4 (2nd February 2023) - Shahid, Marian; Rawls, Ashley; Ramirez, Veronica; Ryman, Sephira; Santini, Veronica E.; Yang, Laurice; Sha, Sharon J.; Hall, Jacob N.; Montine, Thomas J.; Lin, Amy; Tian, Lu; Henderson, Victor W.; et al.
Abstract : Objective: This study was undertaken to study pareidolias, or perceived meaningful objects in a meaningless stimulus, in patients across the Lewy body (LB) disease spectrum, where most do not report hallucinations or delusions. Methods: We studied illusory responses on the Noise Pareidolia Task in 300 participants (38 cognitively impaired LB, 65 cognitively unimpaired LB, 51 Alzheimer disease spectrum [AD‐s], 146 controls). Pairwise between‐group comparisons examined how diagnosis impacts the number of illusory responses. Ordinal regression analysis compared the number of illusory responses across diagnosis groups, adjusting for age, sex, and education. Analyses were repeated after removing participants with reported hallucinations or delusions. Results: Cognitively impaired LB participants were 12.3, 4.9, and 4.6 times more likely than control, cognitively unimpaired LB, and AD‐s participants, respectively, to endorse illusory responses. After adjusting for age, sex, and education, the probability of endorsing 1 or more illusory responses was 61% in the cognitively impaired LB group, compared to 26% in AD‐s, 25% in cognitively unimpaired LB, and 12% in control participants. All results were similar after repeated analysis only in participants without hallucinations or delusions. In LB without hallucinations or delusions, 52% with mild cognitive impairment and 66.7% with dementia endorsed at least 1 illusory response. Interpretation: We found illusory responses are common in cognitively impaired LB patients, including those without any reported psychosis. Our data suggest that, prior to the onset of hallucinations and delusions, the Noise Pareidolia Task can easily be used to screen for unobtrusive pareidolias in all LB patients. ANN NEUROL 2023;93:702–714 Abstract : Pareidolias are perceived meaningful objects in a meaningless stimulus. We studied illusory responses on the Noise Pareidolia Task in Lewy body disease (LBD) with (n = 38) and without (n = 65) cognitive impairment, Alzheimer disease (AD) spectrum (n = 51), and controls (n = 146). Cognitively impaired LBD participants were 12.3, 4.9, and 4.6 times more likely than control, cognitively unimpaired LBD, and AD spectrum participants, respectively, to endorse illusory responses. In LBD without hallucinations or delusions, 52% with mild cognitive impairment and 66.7% with dementia endorsed at least 1 illusory response.